2018
DOI: 10.48550/arxiv.1808.03910
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Knotted boundaries and braid only form of braided belts

Niels Gresnigt

Abstract: The Helon model identifies Standard Model quarks and leptons with certain framed braids joined together at both ends by a connecting node (disk). These surfaces with boundary are called braided 3-belts (or simply belts). Twisting and braiding of ribbons composing braided 3-belts are interchangeable, and it was shown in the literature that any braided 3-belt can be written in a pure twist form, specified by a vector of three multiples of half integers [a, b, c], a topological invariant. This paper identifies th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Care must be taken to account for the permutations induced by braidings when systematically exchanging braiding for twisting [24]. It can likewise be shown that any orientable ribbon braid may be manipulated such that all the twisting of the ribbons is removed, exchanged for braiding [25]. One may write this as [0, 0, 0]B = B[0, 0, 0] where B ∈ B c 3 .…”
Section: Helon Braids As the Basis States Of Minimal Left Ideals Of C...mentioning
confidence: 99%
“…Care must be taken to account for the permutations induced by braidings when systematically exchanging braiding for twisting [24]. It can likewise be shown that any orientable ribbon braid may be manipulated such that all the twisting of the ribbons is removed, exchanged for braiding [25]. One may write this as [0, 0, 0]B = B[0, 0, 0] where B ∈ B c 3 .…”
Section: Helon Braids As the Basis States Of Minimal Left Ideals Of C...mentioning
confidence: 99%